2022
DOI: 10.1109/tnsre.2022.3166181
|View full text |Cite
|
Sign up to set email alerts
|

An Attention-Based Wavelet Convolution Neural Network for Epilepsy EEG Classification

Abstract: As a kind of non-invasive, low-cost, and readily available brain examination, EEG has attached significance to the means of clinical diagnosis of epilepsy. However, the reading of long-term EEG records has brought a heavy burden to neurologists and experts. Therefore, automatic EEG classification for epileptic patients plays an essential role in epilepsy diagnosis and treatment. This paper proposes an Attention Mechanism-based Wavelet Convolution Neural Network for epilepsy EEG classification. Attention Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…DWT is one of the most widely applied wavelet transforms in the field of EEG signal analysis. In [ 20 , 35 , 63 ], DWT was used to obtain most of the brain’s rhythmic frequencies. Wavelet coefficients, named detail and approximation coefficients were extracted to capture the low and high frequencies in the wavelet with a varying number of filter banks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWT is one of the most widely applied wavelet transforms in the field of EEG signal analysis. In [ 20 , 35 , 63 ], DWT was used to obtain most of the brain’s rhythmic frequencies. Wavelet coefficients, named detail and approximation coefficients were extracted to capture the low and high frequencies in the wavelet with a varying number of filter banks.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure results in weighted feature maps corresponding to different channels, where features with high weights are considered more important to the seizure prediction task. A similar concept was introduced in [ 63 , 116 ], but a non-linear softmax activation function was used instead of a sigmoid one. Likewise, in [ 118 , 122 ], the mechanism attends to different channels by learning the attention weights through incorporating multiple layers of convolution layers followed by fully connected layers.…”
Section: Discussionmentioning
confidence: 99%
“…Different from numerous methods [5], [9], [16], [18] . The SPH [33] refers to the intervention period before seizures, where therapies (such as electrical stimulation) could be performed. The SOP indicates the period when seizures are anticipated to occur, which equals the preictal period in duration.…”
Section: B Preprocessingmentioning
confidence: 99%
“…Many literatures [5], [9]- [14] have shown that leading performance could be achieved with DNNs for seizure prediction, in contrast to traditional machine learning methods. Several studies [9], [12], [15], [16] have proposed methods to manually extract features from complex raw EEG, which are widely used to eliminate EEG artifacts. Khan et al [15] processed the raw EEG signal using wavelet transform.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring brain neuron electronic activity is crucial for the treatment of neurological disorders. A routine scalp electroencephalogram (EEG) is considered a better modality for analyzing brain activities [3], [4]. Studies have shown that EEG signals in the interictal period can be measured as the epileptogenic biomarker-interictal epileptiform spike (herein referred to as spike) [5], [6].…”
Section: Introductionmentioning
confidence: 99%